1996
DOI: 10.1159/000147889
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Architectural Changes during Arterial Development and the Role of Hemodynamics

Abstract: Hemodynamics is a major determinant in the anatomical and mural architectural development of the arterial tree. Arterial intimal proliferation commences in utero at specific anatomical sites often appearing eccentric in transverse section and precedes more diffuse concentric thickening. Regarded as an inherent structural component of the wall or an adaptive mural response to increasing hemodynamic stresses concomitant with growth, its occurrence in utero and in lower animals, though generally supportive of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 6 publications
1
30
0
3
Order By: Relevance
“…The tunica intima is composed of a single layer of endothelium that lines the lumen, smooth muscle cells, and connective tissue; the major cell type of the intima is the intimal smooth muscle cell. 1 A surprising number of these arterial intima-enriched genes are also enriched in stratified epithelia, such as the epidermis. 17 A number of these represented precursors of the CE and proteins involved in adhesive junctions.…”
Section: Comparison Of Adult Aorta Gene Expression With Reported Artementioning
confidence: 99%
See 3 more Smart Citations
“…The tunica intima is composed of a single layer of endothelium that lines the lumen, smooth muscle cells, and connective tissue; the major cell type of the intima is the intimal smooth muscle cell. 1 A surprising number of these arterial intima-enriched genes are also enriched in stratified epithelia, such as the epidermis. 17 A number of these represented precursors of the CE and proteins involved in adhesive junctions.…”
Section: Comparison Of Adult Aorta Gene Expression With Reported Artementioning
confidence: 99%
“…1,2 The vena cava and other veins have comparatively thin intima and media and sustain dramatically less pressure. 1 In fact, the predominant vascular feature when a vein is exposed to arterial flow is smooth muscle cell proliferation and matrix deposition that results in intimal thickening.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Cliff [8] suggested that an expansion occurs up to 20% of the diameter of the inner portions and 1% to 4% of the outer portions, although a change of only 10% of radial motion has been proposed [9]. Dobrin [10] reported that the descending thoracic aorta increases longitudinally 1%, while the ascending aorta and pulmonary artery increased from 5 to 11% [11].…”
Section: Mauro Paes Leme De Sá*mentioning
confidence: 99%